2015
DOI: 10.1093/humrep/deu347
|View full text |Cite
|
Sign up to set email alerts
|

Current smoking is associated with lower seminal vesicles and ejaculate volume, despite higher testosterone levels, in male subjects of infertile couples

Abstract: No funding was received for the study. None of the authors have any conflict of interest to declare.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(39 citation statements)
references
References 66 publications
1
35
1
2
Order By: Relevance
“…Despite that human studies are currently few and limited by their observational nature, the existing proof substantiates the claim that marijuana use has a detrimental effect on male reproductive potential [129]. Of interest would also be to explore the confounding effects of marijuana use on tobacco smokers as a recent study revealed that cigarette smokers are greater abusers of cannabis, whilst cigarette smoking males of infertile couples showed lower ejaculate volumes despite higher testosterone levels [130]. All the above findings underline the fact that clinicians should include questions on marijuana usage while evaluating infertility in males.…”
Section: Resultsmentioning
confidence: 99%
“…Despite that human studies are currently few and limited by their observational nature, the existing proof substantiates the claim that marijuana use has a detrimental effect on male reproductive potential [129]. Of interest would also be to explore the confounding effects of marijuana use on tobacco smokers as a recent study revealed that cigarette smokers are greater abusers of cannabis, whilst cigarette smoking males of infertile couples showed lower ejaculate volumes despite higher testosterone levels [130]. All the above findings underline the fact that clinicians should include questions on marijuana usage while evaluating infertility in males.…”
Section: Resultsmentioning
confidence: 99%
“…Lotti et al . () reported that current smoking is associated with lower seminal vesicle volume, despite higher testosterone levels. Moreover, an abstinence period from ejaculation when taking CT is not clear.…”
Section: Discussionmentioning
confidence: 98%
“…Despite the evidence in animal studies of the cytotoxic effect of nicotine and cigarette smoke on Leydig cells, in male smokers a reduction of testosterone levels has not been clearly demonstrated. Conversely, most of the studies found higher testosterone levels in smokers than in non-smokers [38][39][40][41][42]. Higher testosterone and LH levels with higher LH/free testosterone ratio were found with increased smoking, hence authors hypothesized a compensated Leydig cell failure in smokers [40].…”
Section: Effects On Testosterone Productionmentioning
confidence: 98%